PEMBERIAN FASILITAS KEIMIGRASIAN SEBAGAI FAKTOR PENDORONG KEBERHASILAN PENYELENGGARAAN EVENT WISATA BISNIS/MICE INTERNASIONAL - Annisa Wardhani; Christina L. Rudatin; M. Iqbal Katik Rajoendah (Pusat Perencanaan dan Pengembangan Kepariwisataan, 2023)
Business tourism events or better known as MICE events/activities (Meeting, Incentive, Convention and Exhibition) show significant development in Indonesia. Organizing various MICE events and other events on an international scale is able to attract quality international MICE tourists (quality tourists) who spend many times more than ordinary tourists (leisure tourists). This of course has a significant economic impact on destinations organizing international business tourism/MICE events. One of the aspects that drives the success of organizing MICE events on an international scale is the provision of immigration facilities that can simplify immigration procedures for foreign tourists who will attend international events. This immigration facility is provided by Indonesia and other countries to increase the number of international events held, such as providing visa on arrival facilities, single entry visas, temporary visit visas and other forms of ease of procedures. This research will focus on identifying the convenience of immigration facilities and procedures provided by the Indonesian state for foreign tourists who will attend international MICE events. The method used in this research is desk research and case study of international event management. The output of this research is a comprehensive description of the forms of immigration facilities and procedures provided by the Indonesian Government to foreign MICE tourists.